HMGA1 As a Potential Prognostic and Therapeutic Biomarker in Breast Cancer. (26th November 2022) - Wang, Tian; Zhou, Ting; Fu, Fangfang; Han, Yingyan; Li, Yan; Yuan, Ming
Abstract : Background . High-mobility group AT-hook1 (HMGA1) protein plays an important role in various diseases. However, the contribution of HMGA1 in breast cancer remains to be tapped. Methods . The expression of HMGA1 was analyzed in The Cancer Genome Atlas (TCGA) and TIMER database, and immunohistochemistry was performed in 39 breast cancer (BC) patients. The correlation between HMGA1 expression and prognosis was evaluated using Kaplan–Meier plotter (KM plotter) in patients with breast cancer. Then, cBioPortal and bc-GenExMiner were requisitioned to analyze the contribution of HMGA1 expression to clinical features. In order to reveal the function of HMGA1 in breast cancer cells, enrichment analysis was performed using the clusterProfiler R software package. Moreover, CCK8 assay, EdU assay, and Cell Cycle Assay were performed to assess the proliferation, and transwell assay was used to evaluate cell migration and invasion. Flow cytometry was used to explore the role of HMGA1 on cell apoptosis. After that, the effect of HMGA1 on signaling pathways in BC cells was detected by western blot. Results . HMGA1 was highly expressed in a variety of tumors tissues, including BC. High HMGA1 expression was correlated with poor prognosis in BC patients. Meanwhile, HMGA1 expression was increased in molecular phenotypes with poor prognosis (ER-, PR-, and HER2+) and associated with high-grade group, lymph node metastasis, and NPI (Nottingham Prognostic Index). Further, function analysis revealed HMGA1 was enriched in DNA replication and cell cycle pathways in breast cancer. Moreover, knockdown of HMGA1 caused apoptosis, inhibited proliferation, migration, and invasion of MCF-7 and MDA-MB-231 cells, in which the oncogenic signaling pathway of PI3K/AKT/MMP9 played a critical role. Conclusions . HMGA1 was important for breast cancer progression and was a critical prognostic indicator, prompting a potential therapeutic target of breast cancer.